2002
DOI: 10.1183/09031936.02.01552001
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of assisted ventilation in patients with acute respiratory failure

Abstract: The aim of the present study was to verify that the patient/ventilator interaction is similar, regardless of the mode of assisted mechanical ventilation (i.e. pressure-or volume-limited) used, if tidal volume (VT) and peak inspiratory flow (PIF) are matched. Therefore, the authors compared the effects of three different modes of assisted ventilation on the work of breathing (WOB) and gas exchange in patients with acute respiratory failure.For Protocol 1, in seven patients, the authors compared pressure support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…An alternative explanation for the flow-associated reduction in WOB I may arise from the possible effect of flow on the force velocity relationship of the respiratory muscles (19). For a given respiratory muscle output, an increase of peak inspiratory flow per se can contribute to a decrease in the pressure output of the inspiratory muscle in agree- With all the limitations of our approach, our data confirm the importance of an adequate match between the patient's need and the machine initial flow (6,8,15).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An alternative explanation for the flow-associated reduction in WOB I may arise from the possible effect of flow on the force velocity relationship of the respiratory muscles (19). For a given respiratory muscle output, an increase of peak inspiratory flow per se can contribute to a decrease in the pressure output of the inspiratory muscle in agree- With all the limitations of our approach, our data confirm the importance of an adequate match between the patient's need and the machine initial flow (6,8,15).…”
Section: Discussionsupporting
confidence: 80%
“…The WOB I per minute (WOB I min) and WOB per liter (WOB I L) were computed from a modified Campbell diagram, where the elastic recoil pressure of the chest wall was taken at the point of sharp inspiratory deflection of the Pes tracings, that is, the onset of inspiratory effort (14). The chest wall elastance was calculated by plotting Pes against tidal volume while the respiratory muscles were assumed to be in a state of relaxation achieved by a brief period (3-5 mins) of slight hyperventilation during which the patient's inspiratory activity was abolished (15). To exclude errors in computing WOB I and PEEP I due to expiratory muscle activity at the beginning of inspiration, the abrupt decay of Pga from its maximal end expiratory value to its minimal level was measured, and this value was subtracted from the onset of inspiratory effort (i.e., on the Pes tracings) (16).…”
Section: Methodsmentioning
confidence: 99%
“…Rules for setting an optimal rise time, however, are lacking. Notwithstanding this, we should note that studies have shown that both very high and very low rise time may be associated with increased work of breathing [25][26][27][28].…”
Section: Ineffective Triggeringmentioning
confidence: 86%
“…patient-ventilator asynchrony has been observed, mainly due to dissociation between the patient's respiratory effort and ventilator pressure both in terms of timing (uncoupling between the end of mechanical and neural inspiration) and inadequate or excessive assist [14,24]. In addition with pressure support the pressure rise time (defined as the time that pressure reaches the preselected threshold) may influence the synchronization between the patient and the ventilator [25][26][27][28]. In some of the new generation ventilators the rise time is adjustable and this represents a step forward in modulating patientventilator dyssynchrony.…”
Section: Ineffective Triggeringmentioning
confidence: 99%
“…The latest (fourth) generation ventilators were introduced two decades later. The new devices are efficient in responding to patient demand, offer new ventilation modes, allow noninvasive ventilation, have started to incorporate automatic control systems (open lung tools, weaning tools, dual modes), 1 and have enormous monitorization capacities---including onscreen visualization of pressure, flow and volume curves. 2 In addition, the need has recently arisen to introduce telemedicine-based systems as online monitoring tools at the patient bedside.…”
Section: Introductionmentioning
confidence: 99%